2020
DOI: 10.7150/jca.35041
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_100395 inhibits cell proliferation and metastasis in ovarian cancer via regulating miR-1228/p53/epithelial-mesenchymal transition (EMT) axis

Abstract: Purpose: Circular RNAs (circRNAs) have been reported to regulate the incidence of tumor by regulating the transcriptional level and post-transcriptional level of tumor-related genes, and are significantly correlated with tumor metastasis and progression. CircRNA_100395 (circ_100395) has been reported to suppress lung cancer cell proliferation, and might act as an oncogene in deveopment of various cancers. However, the expression and function of circ_100395 in ovarian cancer has not been systematically research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 25 publications
1
58
0
Order By: Relevance
“…Some circRNAs exert their tumor-suppressive roles in OC cells [141][142][143][144][145][146][147][148][149][150] (Table 2 and Figure 4). According to these reports, the "miRNA" sponge seems to be the most common mechanism by which circRNAs regulate the malignant properties of OC cells.…”
Section: Circrnas As Tumor Suppressors In Ocmentioning
confidence: 99%
“…Some circRNAs exert their tumor-suppressive roles in OC cells [141][142][143][144][145][146][147][148][149][150] (Table 2 and Figure 4). According to these reports, the "miRNA" sponge seems to be the most common mechanism by which circRNAs regulate the malignant properties of OC cells.…”
Section: Circrnas As Tumor Suppressors In Ocmentioning
confidence: 99%
“…Furthermore, knockdown of S100A12 participated in the glioma cell apoptosis, which significantly increased the percentage of apoptosis rates in U87 and U251 cell lines. Moreover, silencing of S100A12 also caused the up-regulation of the protein expression of cleaved caspase 3 and Bax and downregulation of Bcl2.These results indicated that S100A12 EMT is a process associated with the invasion and metastasis of cancer, and consequently enhances the metastasis of tumor [18]. Reduced expression of epithelial biomarker E-cadherin and elevated expression of mesenchymal biomarker N-cadherin are the most principal characteristic of EMT [19].…”
Section: Discussionmentioning
confidence: 83%
“…EMT is a process associated with the invasion and metastasis of cancer, and consequently enhances the metastasis of tumor 18 . Reduced expression of epithelial biomarker E-cadherin and elevated expression of mesenchymal biomarker N-cadherin are the most principal characteristic of EMT 19 .…”
Section: Discussionmentioning
confidence: 99%